Training in context of the management group of the educational institution-beyond a technical-bureaucratic relationship - Nogueira, Maria Ephigênia de A Cáceres; Garcia, Andrea Costa (Revista Hipótese, 2018)
The article discusses the relation of the managing group with the school of the municipal education network of São Paulo. It is observed the technical-bureaucratic relationship built with the management group through the regulations of the daily activities of the school. The professional and organizational development aimed at the management team aims at also orienting the units so that they present an internal uniformity of organization and functioning. In order to break with the technical-bureaucratic vision of the role of the school and the management group, we We adopt contextual training, praxeological investigation of the educational process, participation, pedagogical documentation and autonomy for the construction of participative pedagogies necessary for the experience of democratic citizenship.